Host Plant Compatibility Shapes the Proteogenome of Frankia coriariae - Ktari, Amir; Gueddou, Abdellatif; Nouioui, Imen; Miotello, Guylaine; Sarkar, Indrani; Ghodhbane-Gtari, Faten; Sen, Arnab; Armengaud, Jean; Gtari, Maher (Frontiers in Microbiology, 2017)
Molecular signaling networks in the actinorhizal rhizosphere select host-compatible Frankia strains trigger the infection process and eventually the genesis of nitrogen-fixing nodules. The molecular triggers involved remain difficult to ascertain. Root exudates (RE) are highly dy-namic substrates that play key roles in establishing the rhizosphere microbiome. RE are known to induce the secretion by rhizobia of Nod factors, polysaccharides, and other proteins in the case of legume symbiosis. Next-generation proteomic approach was here used to decipher the key bacterial signals matching the first-step recognition of host plant stimuli upon treatment of Frankia coriariae strain BMG5.1 with RE derived from compatible (Coriaria myrtifolia), incompatible (Alnus glutinosa), and non-actinorhizal (Cucumis melo) host plants. The Frankia proteome dynamics were mainly driven by host compatibility. Both metabolism and signal transduction are the dominant activities for BMG5.1 under the different RE conditions tested. A second set of proteins that were solely induced by C. myrtifolia RE and were mainly linked to cell wall remodeling, signal transduction and host signal processing activities. These proteins may footprint early steps in receptive recognition of host stimuli before subsequent events of symbiotic recruitment.